2013
DOI: 10.1186/1747-597x-8-6
|View full text |Cite
|
Sign up to set email alerts
|

Recovery post treatment: plans, barriers and motivators

Abstract: BackgroundThe increasing focus on achieving a sustained recovery from substance use brings with it a need to better understand the factors (recovery capital) that contribute to recovery following treatment. This work examined the factors those in recovery perceive to be barriers to (lack of capital) or facilitators of (presence of capital) sustained recovery post treatment.MethodsA purposive sample of 45 participants was recruited from 11 drug treatment services in northern England. Semi-structured qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 78 publications
3
18
0
Order By: Relevance
“…Moreover, a key cultural adaptation of KKDK was the engagement of family members through the homework and the family modules. Qualitative results highlighted the importance of strengthening family support which is consistent with literature on the important role of family in recovery of users (Duffy & Baldwin, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, a key cultural adaptation of KKDK was the engagement of family members through the homework and the family modules. Qualitative results highlighted the importance of strengthening family support which is consistent with literature on the important role of family in recovery of users (Duffy & Baldwin, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…While previous studies have compared HRQoL between people with dual diagnosis and substance use disorder and/or severe mental illness, no study has examined HRQoL among patients with dual diagnosis and different mental health disorders. Such data could be useful to inform possible targeted treatments for dual diagnosis by providing a subjective complementary perspective to clinicians, reporting unique information about patients’ needs and insights that could enhance the effectiveness of health care [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Duffy and Baldwin in their research aimed at investigating the risk factors for relapse concluded that social support and employment are among important issues to prevent relapse after treatment [29]. Accordingly, it can be said that unemployment during avoidance of drug abuse is one of the main reasons for relapse; therefore, regular follow-up by the therapist and social-family support accompanied by vocational rehabilitation are necessary to prevent relapse [30].…”
Section: The Effect Of Employment On Prevention Of Relapsementioning
confidence: 99%